2002
DOI: 10.1007/s11745-002-0963-6
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid promotes apoptosis in Ramos cells via activation of caspase‐3 and ‐9

Abstract: Eicosapentaenoic acid (EPA; 20:5n-3) may reduce the cell number in cultured leukemia/lymphoma cells owing to reduced cell proliferation, induction of cell death, or a combination of these processes. EPA has been shown to promote apoptosis in Ramos cells, and our present study was focused on a possible cell cycle arrest and the pathways by which the apoptotic process is induced. Apoptosis may proceed along the intrinsic (mitochondrial) or the extrinsic (death receptor) pathway, which are mediated via different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…EPA can be converted to DHA and therefore, it can have effects similar to DHA on cell cycle arrest. Indeed several investigators have demonstrated that EPA also blocks cell cycle progression and induces apoptosis in Ramos cells [98], squamous cell carcinoma [99], vascular smooth muscle cells [75], HT29 colonic cells [100], and pancreatic PaCa-2 cancer cells [101]. In most cases the results are consistent with our finding of growth arrest in the S phase of cell cycle progression [75,100,101] through inhibition of cdk2 activities [75].…”
supporting
confidence: 91%
“…EPA can be converted to DHA and therefore, it can have effects similar to DHA on cell cycle arrest. Indeed several investigators have demonstrated that EPA also blocks cell cycle progression and induces apoptosis in Ramos cells [98], squamous cell carcinoma [99], vascular smooth muscle cells [75], HT29 colonic cells [100], and pancreatic PaCa-2 cancer cells [101]. In most cases the results are consistent with our finding of growth arrest in the S phase of cell cycle progression [75,100,101] through inhibition of cdk2 activities [75].…”
supporting
confidence: 91%
“…Both intrinsic and extrinsic apoptosis pathways have been found to be activated by n-3 PUFAs in different kinds of normal and tumor cells. In particular, it was shown that DHA was able to alter the expression and the activity of caspase-8 and -9 in colon cancer and HL-60 lymphoma cells [59,60]. Moreover, EPA induced an increased activity of caspase-3 and -9 in the lymphoma Ramos cell line [59] and dietary n-3 PUFAs were able to decrease BCL-2 and increase FAS-ligand expression in normal splenic lymphocytes of Balb/c mice [61].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous reports (6,8,28), cell growth was inhibited by EPA-BSA, but no induction of apoptosis was observed. Although n-3 FA-associated apoptosis has been reported in animal models (29,30), in lymphoma (31,32), and colon cancer cells (33,34), data with breast cancer cells are sparse. Chamras et al (28) failed to detect apoptosis in MCF-7 cells treated with EPA and DHA methyl esters.…”
Section: Discussionmentioning
confidence: 99%